2020
DOI: 10.1002/btm2.10172
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potential of extracellular vesicle‐associated long noncoding RNA

Abstract: Both extracellular vesicles (EVs) and long noncoding RNAs (lncRNAs) have been increasingly investigated as biomarkers, pathophysiological mediators, and potential therapeutics. While these two entities have often been studied separately, there are increasing reports of EV-associated lncRNA activity in processes such as oncogenesis as well as tissue repair and regeneration. Given the powerful nature and emerging translational impact of other noncoding RNAs such as microRNA (miRNA) and small interfering RNA, lnc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 111 publications
(177 reference statements)
0
37
0
Order By: Relevance
“…In addition, they are associated with tumorigenesis and tumor microenvironment [ 175 177 ]. Consequently, these unique functions and biology of the EVs in cell-to-cell communications through the delivery of cargo, including mRNAs, miRNAs, and lncRNAs, make them attractive as potential therapeutics and biomarkers in various diseases [ 178 , 179 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they are associated with tumorigenesis and tumor microenvironment [ 175 177 ]. Consequently, these unique functions and biology of the EVs in cell-to-cell communications through the delivery of cargo, including mRNAs, miRNAs, and lncRNAs, make them attractive as potential therapeutics and biomarkers in various diseases [ 178 , 179 ].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of EV research has focused on miRNA, but other RNA species that can be found in EVs include messenger RNA (mRNA), long non-coding RNA (lncRNA), ribosomal RNA (rRNA), transfer RNA (tRNA), RNA repeats, and circular RNA (circRNA) [ 82 , 83 , 84 , 85 , 86 ]. EV cargo can also include DNA and other genetic materials that reflect their cellular origin [ 87 , 88 ].…”
Section: Factors Contributing To Paracrine Benefits Of Mscs and Its Evs In Ischemic Strokementioning
confidence: 99%
“…There is emerging interest in long non-coding RNAs not only as biomarkers but also as therapeutic agents due to their ability to interact with miRNAs. lncRNAs are naturally carried by EVs and are been increasingly documented as key mediators of EV biological effects [ 108 ]. Therapeutic applications of lncRNAs enclosed inside EVs span a broad range including cardiovascular, musculoskeletal, gastrointestinal and nervous system diseases, in which they have demonstrated potential use in mediating tissue regeneration and repair [ 109 , 110 ].…”
Section: Key Points In Exosomes As Drug Delivery Vehiclesmentioning
confidence: 99%